Rhytidhysteron mexicanum sp. nov. (Dothideomycetes, Ascomycota) from the Sierra of Guadalupe, Trans Mexican Volcanic Belt - Cobos-Villagrán, Aurora; Raymundo, Tania; Calvillo-Medina, Rosa Paulina; Valenzuela, Ricardo (Phytotaxa, 2021)
A novel dothideomycete species, Rhytidhysteron mexicanum, is described and illustrated supported by morphological and cultural characters and a phylogenetic analysis (rDNA nucleotide data set). The new species is characterized when immature by boat-shaped hysterothecia (2–4 mm long × 1.5–2.5 mm wide). In mature stage, 2.5–4 mm apothecia with fluted margins remain the same when dry. The epithecium is yellowish green to pistachio green, becoming ocher in the presence of 10% KOH. Ascospores are 34–40(–44) × 10–12(–15) µm, and reddish brown. The morphology of R. mexicanum is compared with other Rhytidhysteron species. A dichotomous key is provided to the five species of Rhytidhysteron known from Mexico.